Long Memory Dynamics for Multivariate Dependence under Heavy Tails - Pawel Janus; Siem Jan Koopman; André Lucas (Tinbergen Institute, 2011)
We develop a new simultaneous time series model for volatility and dependence with long memory (fractionally integrated) dynamics and heavy-tailed densities. Our new multivariate model accounts for typical empirical features in financial time series while being robust to outliers or jumps in the data. In the empirical study for four Dow Jones equities, we find that the degree of memory in the volatilities of the equity return series is similar, while the degree of memory in correlations between the series varies significantly. The forecasts from our model are compared with high-frequency realised volatility and dependence measures. The forecast accuracy is overall higher compared to those from some well-known competing benchmark models.
urn:NBN:nl:ui:31-1871/38566
Keywords: C10; C22; C32; C51; 330; fractional integration; correlation; Student's t copula; time-varying dependence; multivariate volatility